UPAYA MENINGKATKAN KEMAMPUAN SISWA SMP DALAM MEMAHAMI TEKS LISAN DAN TULIS PADA PEMBELAJARAN BAHASA INGGRIS MELALUI MEDIA AUDIO VISUAL - Fauziah Rasyid; Mega Irhamna (Jurnal Dedikasi Pendidikan, 2021)
The low ability to understand students' texts, especially in English lessons, has long been a burden on the minds of researchers. Many students are not able to do understanding properly and correctly. In the evaluation, many student scores are below the KKM. Students seem less enthusiastic and not ready to take lessons on conversational material so that the class atmosphere becomes passive and conventional and non-variative learning. This classroom action research aims: To find out the increase in understanding of grade VIII-1 students in the odd semester of SMP Negeri 2 Deli Tua in the application of Audio Visual Strategy. This research was carried out using descriptive qualitative methods and class action research approaches, which were carried out in 2 cycles. Each cycle includes planning, implementation, observation and reflection, while the subjects of this class action research are class VIII students in the odd semester of SMP Negeri 2 Deli Tua. While the object is the Audio Visual Strategy. From the research conducted by examining the initial conditions of students as measured by written tests and the results of classroom action research with 2 cycles, it was seen that there was an increase in the learning outcomes achieved by students in mastering the material. Based on data analysis, it can be concluded that in cycle 1, students' learning completeness in this material average value is only 69.29, while in cycle 2 by applying Audio Visual Strategy, the average value increases in cycle 2 to 87.14..